1993
DOI: 10.1523/jneurosci.13-08-03284.1993
|View full text |Cite
|
Sign up to set email alerts
|

The slow (< 1 Hz) oscillation in reticular thalamic and thalamocortical neurons: scenario of sleep rhythm generation in interacting thalamic and neocortical networks

Abstract: As most afferent axons to the thalamus originate in the cerebral cortex, we assumed that the slow (< 1 Hz) cortical oscillation described in the two companion articles is reflected in reticular (RE) thalamic and thalamocortical cells. We hypothesized that the cortically generated slow rhythm would appear in the thalamus in conjunction with delta and spindle oscillations arising from intrinsic and network properties of thalamic neurons. Intracellular recordings have been obtained in anesthetized cats from RE (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
492
3
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 650 publications
(537 citation statements)
references
References 45 publications
39
492
3
3
Order By: Relevance
“…With respect to the functional connectivity to the dorsal margin of the thalamus, albeit speculative, one may assume that this thalamic region represents the thalamic reticular nucleus (Viviano and Schneider, 2015; Zikopoulos and Barbas, 2006; Jones, 1985), a layer of GABAergic cells wrapping the dorsolateral segments of the thalamus (Jones, 1985; Zikopoulos and Barbas, 2006). GABAergic neurons in the thalamic reticular nucleus modulate both corticothalamic and thalamocortical communications (Slotnick, Moo, Kraut, Lesser, & Hart, 2002; Lozsádi, 1995; Steriade, Contreras, Curró Dossi, & Nuñez, 1993; Jones, 1985). For instance, the thalamic reticular nucleus receives excitatory inputs from cortex and other thalamic nuclei and sends inhibitory projections (GABAergic) back to thalamic nuclei thereby controlling the activity/oscillations in thalamocortical loops (Slotnick et al, 2002; Lozsádi, 1995; Steriade et al,1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the functional connectivity to the dorsal margin of the thalamus, albeit speculative, one may assume that this thalamic region represents the thalamic reticular nucleus (Viviano and Schneider, 2015; Zikopoulos and Barbas, 2006; Jones, 1985), a layer of GABAergic cells wrapping the dorsolateral segments of the thalamus (Jones, 1985; Zikopoulos and Barbas, 2006). GABAergic neurons in the thalamic reticular nucleus modulate both corticothalamic and thalamocortical communications (Slotnick, Moo, Kraut, Lesser, & Hart, 2002; Lozsádi, 1995; Steriade, Contreras, Curró Dossi, & Nuñez, 1993; Jones, 1985). For instance, the thalamic reticular nucleus receives excitatory inputs from cortex and other thalamic nuclei and sends inhibitory projections (GABAergic) back to thalamic nuclei thereby controlling the activity/oscillations in thalamocortical loops (Slotnick et al, 2002; Lozsádi, 1995; Steriade et al,1993).…”
Section: Discussionmentioning
confidence: 99%
“…GABAergic neurons in the thalamic reticular nucleus modulate both corticothalamic and thalamocortical communications (Slotnick, Moo, Kraut, Lesser, & Hart, 2002; Lozsádi, 1995; Steriade, Contreras, Curró Dossi, & Nuñez, 1993; Jones, 1985). For instance, the thalamic reticular nucleus receives excitatory inputs from cortex and other thalamic nuclei and sends inhibitory projections (GABAergic) back to thalamic nuclei thereby controlling the activity/oscillations in thalamocortical loops (Slotnick et al, 2002; Lozsádi, 1995; Steriade et al,1993). Brain oscillations result in synaptic plasticity via synchronizing and desynchronizing neural assemblies and are therefore one of the core mechanisms underlying episodic memory (Hanslmayr, Staresina, & Bowman, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…TRN projections to the intralaminar and midline nuclei are more diffuse than the reticular projection to the specific dorsal thalamic nuclei. The TRN influences the sleep/wake cycle (Steriade et al, 1993), the efficacy of thalamic inputs to the cortex (Nicolelis and Fanselow, 2002;Swadlow et al, 2002), and attention (Sherman and Guillery, 2001). …”
Section: 21mentioning
confidence: 99%
“…Pioneering work by Steriade and colleagues has shown that identified neurons in a number of different cortical areas fluctuate between depolarized (UP) and hyperpolarized (DOWN) states[29,30,31]. The UP state is characterized by barrages of synaptic activity, a plateau depolarization, and action potential firing, while the DOWN state is characterized by cell hyperpolarization and silence[30] (Fig.…”
Section: Neuronal Substrates Of Slow Oscillationsmentioning
confidence: 99%
“…In SWS, the thalamocortical system is dominated by stereotyped field potential oscillations in the 0.5- to 4-Hz frequency range, which includes the slow (<1 Hz) oscillation and delta frequencies (1–4 Hz). Analytically described by Steriade and colleagues 17 years ago[29,30,31], the slow oscillation is now thought to be one of the primary organizers of network activity in the thalamocortical system[32] and possibly the key player in off-line memory consolidation during sleep[10,21,26]. In the remainder of this review, we will first discuss the neuronal mechanisms underlying slow oscillations, highlighting the role of dynamic cortico- and thalamocortical coupling to generate this network activity.…”
Section: Introductionmentioning
confidence: 99%